SCIENTIFIC AND PRACTICAL BASES OF INCREASING THE EFFICIENCY OF LIVESTOCK IN THE CONDITIONS OF CENTRAL KAZAKHSTAN - Sarkhanov Kakimzhan Akhmedzhanovich (Academic Journal of Physical and Chemical Sciences, 2021)
The analysis demonstrates that the growth of animal products is provided, mainly by the private subsidiary farmings and households (PSF and HH), where is concentrated more than 80% of cattle and poultry. Meanwhile, small-scale seasonal production prevails in this sector, which, as practice shows, sometimes does not meet the requirements of the processing industry, and the output products cannot be competitive domestically, especially on the foreign markets. Consequently, the purpose of these scientific and production researches were the development of the conceptual framework for the improvement of the efficiency of live-stock animal breeding in the rural regions of Central Kazakhstan, which have lion shares of pasture land and underground minerals of the country. A distinctive feature of the operating system of the small economy management forms in rural regions of Akmola, Karaganda, North-Kazakhstani, and South-Kazakhstani areas has been studied. The modern abstract-logical, economic-mathematical and statistical methods, common research methods in the area of livestock section are applied in the scientific researches, experiments: All-Russia Research and Development Institute of Livestock Breeding, VIZH, VASKHNIL, and also data on the development of cattle breeding of the region before and post-privatization periods of the rural reform was used. On the basis of long-term research work, the author having identified the main problems, is developing a comprehensive program for the development of animal husbandry in four areas, that is, to improve systems: economy management, fodder production, subsidies and breeding. According to the research, the principles and conceptual foundations of improving the efficiency of breeding domestic farm animals have been developed. At the same time, the principles of a systematic approach, feedback, the need to describe the regulatory impacts of the state, the functional composition and structure of the system of economic models at the level of rural regions are distinguished and justified.